“No Papers. No Doctor”: A Qualitative Study of Access to Maternity Care Services for Undocumented Immigrant Women in Denmark - Funge, Julia Kadin (Int J Environ Res Public Health, 2020)
The purpose of this study is to explore undocumented immigrant women’s experiences of, as well as their access to, maternity care services during pregnancy in Denmark. Recruiting through the two branches of a non-governmental organization (NGO)-driven health clinic in Denmark, we conducted 21 semi-structured interviews with undocumented immigrant women in Denmark from January 2018 to January 2019. The undocumented immigrant women experienced barriers such as fear of deportation, concerns about payment for services, and uncertainties about rules for access. Many of them described depending on NGO-driven initiatives to access maternity care services and found these as providing a safe environment for care. Our findings contribute insights towards understanding the health behavior of undocumented immigrant women and highlight the need for inclusive care to safeguard the health of the women and their children.